Helping a Man With Cerebral Palsy Access Preferred Internet Content Using Assistive Technology and a Participant-Directed Support Model. (December 2017) - Sigafoos, Jeff; Carnett, Amarie; McNamee, Stephanie; Lancioni, Giulio E.; O'Reilly, Mark F.
A man with cerebral palsy was helped to access preferred Internet content through a treatment program involving assistive technology and support from research staff. The assistive technology included an individually configured Apple iPad® and a head pointer that enabled the man to directly select screen icons linked to preferred websites. Staff supported the man by setting up the technology and responding to his instructions and requests for assistance and by performing general troubleshooting operations (e.g., starting up, positioning, rebooting, and charging the iPad® as necessary). Twelve treatment sessions, one per week, provided opportunities for the man to practice using the iPad®. Progress was assessed by rating his (a) degree of independence, (b) level of participation, (c) performance, (d) satisfaction with performance, and (e) overall satisfaction with the head pointer, the iPad®, and the treatment program. The man actively participated in each treatment session and reported better performance over the course of treatment. He was also generally satisfied with the program. The present combination of assistive technology and staff support appeared acceptable and effective in increasing participation. The approach illustrates how aspects of self-determination can be incorporated into assistive technology interventions for adults with cerebral palsy.